Genetic variants of the p53 and p73 genes jointly increase risk of second primary malignancies in patients after index squamous cell carcinoma of the head and neck - Zhang, Yang (2011)
BACKGROUND: Due to the structural and biochemical similarities between the anti-tumor p53 and p73 proteins, we hypothesized that individuals who carry high risk genotypes of p53 codon 72 and p73 G4C14-to-A4T14 polymorphisms have a higher risk of developing second primary malignancy (SPM) in patients after an index squamous cell carcinomas of the head and neck (SCCHN). METHODS: A cohort of 1,269 patients with index cases of SCCHN was recruited between May 1995 and January 2007 at M.D. Anderson Cancer Center and followed for SPM development. Patients were genotyped for p53 codon 72 and p73 G4C14-to-A4T14 polymorphisms. A log-rank test and Cox proportional hazard models were used to compare SPM-free survival and SPM risk among different risk groups with the combined risk genotypes of the two polymorphisms. RESULTS: Our data demonstrated that patients with p53 WP + PP and p73 GC/GC genotypes had a worse SPM-free survival and an increased SPM risk compared with the corresponding p53 WW and p73 GC/AT +AT/AT genotypes. After combining the two polymorphisms, a borderline significantly or significantly reduced SPM-free survival and increased SPM risk were observed in medium-risk group (p53 WW and p73 GC/GC or p53 P carrier and p73 AT carriers) and high-risk group (p53 P carriers and p73 GC/GC) compared with low-risk group (p53 WW and p73 AT carriers), respectively. CONCLUSIONS: Our results suggest an increased risk of SPM after index SCCHN with both p53 and p73 polymorphisms individually and in combination.